2018
DOI: 10.1108/cms-07-2017-0211
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and employee well-being

Abstract: Purpose Considering work and family responsibility has become an important issue due to changes in the lives of people, understanding work and family responsibilities is essential for organizations in assisting employees to increase their well-being. Therefore, the purpose of this paper is to find the impact of perceived organizational support (POS) on work–family facilitation (WFF) and work–family conflict (WFC) and eventually on employee well-being. Design/methodology/approach A survey questionnaire is adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…For example, Cassidy et al (2017) stated that providing a supportive work environment and conditions for preschool teachers and giving them more care would be conducive to relieving work stress and engaging in work with more positive emotions and more energy, thus promoting high levels of work well-being. Moreover, the study by Wattoo et al (2018) confirmed that the feeling of organizational support was significantly and positively related to job well-being. Therefore, the results of this study are consistent with previous studies.…”
Section: Perceived Organizational Support Negatively Predicted Job St...mentioning
confidence: 70%
“…For example, Cassidy et al (2017) stated that providing a supportive work environment and conditions for preschool teachers and giving them more care would be conducive to relieving work stress and engaging in work with more positive emotions and more energy, thus promoting high levels of work well-being. Moreover, the study by Wattoo et al (2018) confirmed that the feeling of organizational support was significantly and positively related to job well-being. Therefore, the results of this study are consistent with previous studies.…”
Section: Perceived Organizational Support Negatively Predicted Job St...mentioning
confidence: 70%
“…Empirical evidence shows that POS is positively related to positive attitudes and behaviors at the workplace, such as employee performance (Li et al, 2019), work engagement (Imran et al, 2020), affective commitment (Nazir et al, 2018), psychological empowerment and job satisfaction (Maan et al, 2020). Other studies reveal that POS decreases not only burnout and turnover intention of employees (Wang and Wang, 2020) but also work-family conflict (Wattoo et al, 2018). Generally, therefore, POS creates a positive work environment for employees.…”
Section: Perceived Organizational Support and Career Successmentioning
confidence: 99%
“…Analogous results were obtained for family support and family satisfaction through FWE (Lu et al, 2015;Nicklin and McNall, 2013). Work and family resources via WFE and few, respectively, benefitted domain unspecific outcomes like employee well-being (Annor, 2016;Wattoo et al, 2018). Further, mediation was confirmed for transformational leadership and organizational commitment (Gillet et al, 2016), ethical leadership and life satisfaction (Zhang and Tu, 2018).…”
Section: Mediating Role Of Work-family Enrichmentmentioning
confidence: 58%